Caracterização dos defeitos pontuais e das propriedades fosforescentes do silicato de cádmio - Farias, Damon Ferreira (2018)
Cadmium silicate in composition CdSiO3 is a phosphorescent material with potential applications in areas such as emergency lights, opto-electronic devices and coating of ceramic tiles for use in radiodiagnostic rooms. In this work, the main goal was to investigate the mechanism of intrinsic luminescence of the crystalline material CdSiO3 evaluating the influence of the synthesis parameters on the structure of the material and its optical properties. The effects of the synthesis parameters (pH, calcination temperature and time) were investigated to obtain best synthesis conditions for sample preparation. Samples with single crystalline phase have been successfully obtained using starting solutions with pH of 1.0, 3.0 and 7.0, with minimum temperature and time of calcination equal to 1000 °C/3h or 700 °C/3h for samples departing from solutions pH 1.0 or 7.0, respectively. The optical properties of the synthesized powders were studied by a combination of Optical Absorption (OA), Photoluminescence (PL), thermoluminescence (TL) and luminescent decay. Absorption spectra revealed a self-trapped exciton band characteristic of CdSiO3 at around 4.70 eV, and a dependency of the bandgap energy on the starting pH used, being 5.37 eV or 5.62 eV for pH 7.0 or 1.0, respectively. Luminescence emission spectra are composed of two main bands at 590 nm and 490 nm, with varied relative intensities with the synthesis parameters. A band at 460 nm with higher intensity was observed from the sample produced from solution with pH = 1.0, while a band at 590 nm with higher intensity corresponds to the one produced with pH 7.0. The band at 590 nm of the sample produced from solution with pH = 7.0 presented higher light persistence, which was related to defects in the Si network, in addition to the vacancy effects Cd and O. In this work, we verified that the light emission can be improved by adjusting the pH during the sol-gel synthesis and made possible the understanding of the influence of the pH on the crystalline phase formation and its effect on the defects produced and the optical properties of the material.